A method for estimating gap-junctional conductance between ca3 hippocampal pyramidal neurons - Poznanski, R.R.; Ng, L.S.; Woo, C.S. (2010)
Coupling ratio analysis using dual intracellular recording combined with ultrastructural examination of particles in plaques corresponding to gap-junctional channels is a quantitative measure of electrotonic coupling. The difficulty in combining both electrophysiological and morphological methods in determining the gap-junctional conductance of electrical synapses is addressed through the use of a passive cable model of two electrotonically coupled CA3 hippocampal pyramidal cells. Cable estimates of the gap-junctional coupling conductance based on electrophysiological data are combined with freeze-fracture replicas of connexin channels (gap-junctions) to confirm strong coupling between the somata of CA3 pyramidal neurons, based on the assumption that the electrical synapse works as an ohmic resistor influenced by an ensemble of unitary resistances of gap-junctional channels.